Patient-reported utilization patterns of endometriosis medications in Europe: Real-world results from the non-interventional VIPOS study. Issue 4 (December 2021) - Becker, Kerstin; Heinemann, Klaas; Imthurn, Bruno; Marions, Lena; Moehner, Sabine; von Stockum, Sophia; Gerlinger, Christoph; Serrani, Marco; Faustmann, Thomas
Introduction: Women with endometriosis require individualized, long-term treatment. Analyzing prescription choices, medication switches, discontinuations, and breaks can describe real-world treatment patterns and optimize pathways for women. To our knowledge, theVi sanneP ost-approvalO bservationalS tudy (VIPOS) is the largest real-world, non-interventional study examining the safety of hormonal treatments for the routine clinical management of endometriosis. We present data from VIPOS on endometriosis drug utilization patterns, including treatment discontinuation due to treatment failure. Methods: VIPOS was a prospective, long-term, controlled, non-interventional cohort study in six European countries (Germany, Switzerland, Russia, Poland, Ukraine, and Hungary) conducted between 2010 and 2018. Women self-reported medical and gynecological history and symptoms and treatment information via comprehensive questionnaires. Results: Overall, 27, 840 women were enrolled via gynecologists or specialized centers. Inter-country variance in treatment prescription patterns suggests the influence of differential management strategies and guidelines on prescribing behavior and diagnostic methods. Most enrolled women were receiving combined hormonal contraceptives. Women receiving dienogest 2 mg or gonadotropin-releasing hormone agonists more often had a surgical diagnosis of endometriosis compared to other treatments, while most women receiving combined hormonal contraceptives, other progestins or danazol had a symptom-based diagnosis. Although treatment changes during follow-up were common, only 4733 discontinuations out of 42, 342 treatment starts were reported due to side effects or treatment ineffectiveness. Conclusion: VIPOS provides valuable insights into the considerable inter-country variance in endometriosis treatment prescription and potential role of differing management guidelines and practices strategies. Findings presented here suggest the need greater alignment of clinical practice to optimize patient management.